Aggressive pituitary neuroendocrine tumors: current practices, controversies, and perspectives, on behalf of the EANS skull base section - Ng, Sam; Messerer, Mahmoud; Engelhardt, Julien; Bruneau, Michael; Cornelius, Jan Frederick; Cavallo, Luigi Maria; Cossu, Giulia; Froelich, Sebastien; Meling, Torstein R.; Paraskevopoulos, Dimitrios; Schroeder, Henry W. S.; Tatagiba, Marcos; et al. (Acta Neurochirurgica, 2021)
Aggressive pituitary neuroendocrine tumors (APT) account for 10% of pituitary tumors. Their management is a rapidly evolving field of clinical research and has led pituitary teams to shift toward a neuro-oncological-like approach. The new terminology “Pituitary neuroendocrine tumors” (PitNet) that was recently proposed to replace “pituitary adenomas” reflects this change of paradigm. In this narrative review, we aim to provide a state of the art of actual knowledge, controversies, and recommendations in the management of APT. We propose an overview of current prognostic markers, including the recent five-tiered clinicopathological classification. We further establish and discuss the following recommendations from a neurosurgical perspective: (i) surgery and multi-staged surgeries (without or with parasellar resection in symptomatic patients) should be discussed at each stage of the disease, because it may potentialize adjuvant medical therapies; (ii) temozolomide is effective in most patients, although 30% of patients are non-responders and the optimal timeline to initiate and interrupt this treatment remains questionable; (iii) some patients with selected clinicopathological profiles may benefit from an earlier local radiotherapy and/or chemotherapy; (iv) novel therapies such as VEGF-targeted therapies and anti-CTLA-4/anti-PD1 immunotherapies are promising and should be discussed as 2nd or 3rd line of treatment. Finally, whether neurosurgeons have to operate on “pituitary adenomas” or “PitNets,” their role and expertise remain crucial at each stage of the disease, prompting our community to deal with evolving concepts and therapeutic resources.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Aggressive pituitary adenoma; Atypical pituitary adenoma; Endocrine tumors; Neuro-oncology; PitNet; Pituitary carcinoma; Radiotherapy; Temozolomide; Transsphenoidal surgery